2008
DOI: 10.1016/j.jnucmat.2008.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Ductile–brittle transition of polycrystalline iron and iron–chromium alloys

Abstract: a b s t r a c tFracture toughness of polycrystalline Fe, Fe-3%Cr and Fe-9%Cr was measured by four-point bending of pre-cracked specimens at temperatures between 77 K and 150 K and strain rates between 4.46 Â 10 À4 and 2.23 Â 10 À2 s À1 . For all materials, fracture behaviour changed with increasing temperature from brittle to ductile at a distinct brittle-ductile transition temperature (T c ), which increased with increasing strain rate. At low strain rates, an Arrhenius relation was found between T c and stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The fracture mechanism of nanocrystalline bcc iron is very different from that of coarse-grained iron under a high loading rate. Experimental results show that the fracture behavior of coarse-grained iron is determined by the twinning onset and dislocation motion at the crack tip under high loading rates [ 46 ]. There is no evidence that grain boundaries far from the crack tip provide sites for plastic deformation during the fracture process of coarse-grained iron specimens with a sharp crack.…”
Section: Resultsmentioning
confidence: 99%
“…The fracture mechanism of nanocrystalline bcc iron is very different from that of coarse-grained iron under a high loading rate. Experimental results show that the fracture behavior of coarse-grained iron is determined by the twinning onset and dislocation motion at the crack tip under high loading rates [ 46 ]. There is no evidence that grain boundaries far from the crack tip provide sites for plastic deformation during the fracture process of coarse-grained iron specimens with a sharp crack.…”
Section: Resultsmentioning
confidence: 99%
“…The result of present study is deviated from the regression line drown form the other points. Other data are from: Si 14) , GaAs 35) , Ge 9) , Al 2 O 3 15) , Mo 36) , SiC 37) , TiAl 10) , diamond 38) , Fe-3%Si 39) , V 40) , Fe 41,42) . …”
Section: 実験方法mentioning
confidence: 99%
“…[8][9][10] Many pioneering works [11][12][13][14][15] have been performed to elucidate the fundamental mechanism behind the BDT by using silicon single crystals since St. John 1) demonstrated that they showed very sharp transition behaviour and strong deformation rate dependence of the BDT temperature. It suggests that the controlling process of the BDT behaviour is a thermally activated process so that the activation energy was obtained from the deformation rate dependence of the transition temperature.…”
Section: Introductionmentioning
confidence: 99%